Erste Begegnung. - Eke, Norbert (Literatur in Westfalen. Beiträge zur Forschung 20.)

IBB: Fast Burrows-Wheeler Transform Construction for Length-Diverse DNA Data - Adler, Enno; Böttcher, Stefan; Hartel, Rita; Steininger, Cedric Alexander (23rd International Symposium on Experimental Algorithms)

Der Abgrund in deutscher und baltischer Kultur / The Abyss in German and Baltic Culture. Hg. von Marko Pajević und Jaanus Sooväli.

Julia Menzel: Holocaust, Zeit und Erzählung. Traumatische Zeiterfahrung in H. G. Adlers Roman Eine Reise.

Izabela Rakar: Verbreiterte Breitenwirkung. Thomas Kling, seine Vorgänger, Zeitgenossen und Nachfolger

Jakub Gortat: Remembering National Socialism in Austrian Post-war Film (1945-1955).

Don't Touch the Power Line - A Proof-of-Concept for Aligned LLM-Based Assistance Systems to Support the Maintenance in the Electricity Distribution System - Kaltenpoth, Sascha; Müller, Oliver (ACM SIGEnergy Energy Informatics Review)
As a possible solution to the demographic change and the resulting knowledge loss due to retirements in the Energy sector, this study aimed to develop a generic pipeline to implement and evaluate proof-of-concepts (PoCs) for LLM-based assistance systems in new domains. Our pipeline contains an LLM-based data generation strategy based on documents, a retrieval-augmented generation (RAG) architecture utilizing prompting techniques on existing German LLMs, and an LLM-based automatic evaluation strategy. We leverage our pipeline to evaluate five LLMs using data from a German DSO. We found that the Llama3 and the Mistral model are appropriately aligned for the task. We plan to pilot the RAG architecture in the DSO's infrastructure for future research and continuously research improvements using the generated human demonstrations.

A Step Towards Cognitive Automation: Integrating LLM Agents with Process Rules - Kaltenpoth, Sascha Benjamin; Skolik, Alexander Marcus; Müller, Oliver; Beverungen, Daniel (Lecture Notes in Computer Science)

Hermann, Michael, „Der Wandel von Statistik zu Maschinellem Lernen“, SieB. Siegener Beiträge zur Geschichte und Philosophie der Mathematik 17 (2023), 145–179. - Peckhaus, Volker (zbMATH Open, Zbl. 07925543)

EU-Projekt CREXDATA: Erkenntnisse und Handlungsempfehlungen zum Einsatz KI-generierter Lageinformationen für die Lagebewertung und Maßnahmenplanung in Extremwetterlagen - Pottebaum, Jens; Gräßler, Iris; Ebel, Marcel; Özcan, Deniz; Döhner, Niklas; Pratzler-Wanczura, Sylvia; Derin, Enes; Krüger, Oliver; Kruijff-Korbayova, Ivana; Stampa, Merlin

Visualization Task Taxonomy to Understand the Fuzzing Internals - Kummita, Sriteja; Miao, Miao; Bodden, Eric; Wei, Shiyi (ACM Transactions on Software Engineering and Methodology)
Greybox fuzzing is used extensively in research and practice. There are umpteen publications that improve greybox fuzzing. However, to what extent do these improvements affect the internal components or internals of a given fuzzer is not yet understood as the improvements are mostly evaluated using code coverage and bug finding capability. Such an evaluation is insufficient to understand the effect of improvements on the fuzzer internals. Some of the literature visualizes the outcomes of fuzzing to enhance the understanding. However, they only focus on high-level information and no previous research on visualization has been dedicated to understanding fuzzing internals. To close this gap, we propose the first step towards development of a fuzzing-specific visualization framework: a taxonomy of visualization analysis tasks that fuzzing experts desire to help them understand the fuzzing internals. Our approach involves conducting interviews with fuzzing experts and using qualitative data analysis to systematically extract the task taxonomy from the interview data. We also evaluate the support of existing fuzzing visualization tools through the lens of our taxonomy. In our study, we have conducted 33 interviews with fuzzing practitioners and extracted a taxonomy of 120 visualization analysis tasks. Our evaluation shows that the existing fuzzing visualization tools only provide aids to support 10 of them.

The Need for Diffraction in STEM -fields: An Ethical Feminist Consideration of the Concept of Genderscripting - Grewe, Felix (Feminist Encounters Special Issue on Peripheral Visions of Alternative Futures: Feminist Techno-imaginaries)

Entrepreneurship Education at All Levels of Education: A Systematic Literature Review - Liszt-Rohlf, Verena; Büker, Ronja; Kamsker, Susanne (21th Biennial EARLI Conference)

Vernetzte Musikquellen des 19. Jahrhunderts. Überlegungen zum Zusammenspiel wissenschaftlicher Editionen mit RISM am Beispiel des Stuttgarter Faust 1832 - Frömmel, Lena; Münzmay, Andreas (Musikquellen des 19. Jahrhunderts in Deutschland. Herausforderungen und Chancen)
This article explores the challenges and opportunities of documenting and cataloguing 19th-century music sources in Germany, using the 1832 Stuttgart production of Goethe’s Faust with music by Peter Joseph von Lindpaintner as a case study. The main focus lies on the potential interplay between (digital) critical music editions and RISM as complementary approaches to source documentation. While RISM has traditionally concentrated on pre-1800 sources, the vast and complex landscape of 19th-century music-theatrical materials—especially handwritten performance materials, but also printed sources—calls for new collaborative strategies. Drawing on the Faust edition within the OPEN Edirom project, which publishes data in open, structured formats (TEI and MEI) and makes them accessible via the RADAR4Culture repository and the Culture Knowledge Graph, the article argues for closer integration between editorial projects and RISM through stable identifiers and Linked Open Data principles. Editorial descriptions do not compete with RISM records but meaningfully extend them, and vice versa. The case study illustrates how editorial source descriptions and full-text editions could enhance the informational scope and augment the reach of RISM, and how RISM could serve as a basis for more granular, interconnected, and FAIR-compliant musicological research infrastructures. The article proposes RISM as a central access point for distributed research data and outlines the simple yet effective steps researchers can take to enhance discoverability and interoperability: namely, by using (or if necessary, creating) RISM IDs and by publishing data with persistent Digital Object Identifiers (DOIs).

Jitter in photon-number-resolved detection by superconducting nanowires - Sidorova, Mariia; Schapeler, Timon; Semenov, Alexej D.; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Photonics)
By analyzing the physics of multi-photon absorption in superconducting nanowire single-photon detectors (SNSPDs), we identify physical components of jitter. From this, we formulate a quantitative physical model of the multi-photon detector response that combines the local detection mechanism and local fluctuations (hotspot formation and intrinsic jitter) with the thermoelectric dynamics of resistive domains. Our model provides an excellent description of the arrival-time histogram of a commercial SNSPD across several orders of magnitude, both in arrival-time probability and across mean photon number. This is achieved with just three fitting parameters: the scaling of the mean arrival time of voltage response pulses, as well as the Gaussian and exponential jitter components. Our findings have important implications for photon-number-resolving detector design, as well as applications requiring low jitter, such as light detection and ranging (LIDAR).
Keywords: Jitter; PNR; SNSPD

Peter Joseph von Lindpaintner, Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann (1832)
The present OPEN Edirom digital edition of Goethe’s Faust presents the literary and musical text of the work as it was possibly performed at its premiere (Friday, March 2, 1832) and consecutive performances under the direction and participation of Carl Seydelmann (directing the production and playing the role of Mephistopheles) and Peter Joseph von Lindpainter in the Stuttgart Hoftheater in 1832 (March 11, May 28, October 12) and 1833 (May 14, December 27), in accordance with the surviving sources, i.e., the original theatre material preserved in the Württemberg State Library in Stuttgart (D-Sl). This material constitutes a nearly complete autograph source package consisting of text adaptation (an autograph by Seydelmann incorporated into a copy of the print edition published by Cotta in Tübingen in 1830) and corresponding music (two volumes with autograph scores by Lindpaintner).

Mit KI (Elicit) den Forschungsstand beschreiben – ein kritischer Erfahrungsbericht - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Participatory Research with Teachers - A Critical Analysis of Power Dynamics - Schmidt, Rebecca (Transdisziplinäre Räume in den Kulturwissenschaften)

Aufruhr im Raum der Räume: Logik zwischen Philosophie und Mathematik - Peckhaus, Volker (Transdisziplinäre Räume in den Kulturwissenschaften)

Eckes, Christophe, “Philosophical and Mathematical Duality in Albert Lautman’s Work”, in: R. Krömer und E. Haffner (Hgg.), Duality in 19th and 20th Century Mathematical Thinking, Cham: Birkhäuser 2024 (Science Networks. Historical Studies; 63), 435–469. - Peckhaus, Volker (zbMATH Open, Zbl. 07951350)